2017
DOI: 10.1007/s00520-017-3592-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of totally implantable venous access devices

Abstract: PABSI was the most common reason for premature catheter removal, with a varied incidence rate between different cancer types. Suboptimal tip position was also a risk factor. Confirming the final tip position after implantation is crucial. Infection control is important for TIVAD care, especially in high-risk cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…The overall postoperative complication rate in this study was 4.48% (3/67), which was lower than that in most other studies [12, 24]. Catheter-related infections were found in 1 case 5 weeks after surgery.…”
Section: Discussioncontrasting
confidence: 63%
“…The overall postoperative complication rate in this study was 4.48% (3/67), which was lower than that in most other studies [12, 24]. Catheter-related infections were found in 1 case 5 weeks after surgery.…”
Section: Discussioncontrasting
confidence: 63%
“…Retrospective studies of Wang et al [5] involving 235 cases reported that the mean age of cases was 58.2 years, 62.5% being female. Totally implantable venous port catheter was applied most commonly in breast, lung and colorectal cancer cases.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that there was no significant difference in infection rate when antibiotic prophylaxis was used. Similarly, Wang et al [5] reported that the principal reasons for premature catheter removal were port-associated blood stream infection and a suboptimal tip position. The port-associated blood stream infection was more prevalent in hematologic and upper gastrointestinal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common TIVAD-related complications in patients with cystic fibrosis include occlusion, infection, leakage, pain or discomfort, venous thrombosis, stenosis, and port extrusion [ 7 , 8 ]. In patients with cancer, common TIVAD complications include infection, sepsis, thrombosis, skin dehiscence, and pain [ 6 , 9 , 10 ]. While some overlap exists, the complication profile for TIVAD use for LSDs is unique.…”
Section: Discussionmentioning
confidence: 99%